The Regulatory Role of Both MBNL1 and MBNL1-AS1 in Several Common Cancers - Zhang, Qi; Wu, Yinxin; Chen, Jinlan; Tan, Fangshun; Mou, Jie; Du, Zhuoying; Cai, Yuxuan; Wang, Bei; Yuan, Chengfu (Current Pharmaceutical Design, 2022)
Background: Muscle blind-like-proteins (MBNL) are a class of tissue-specific RNA metabolism regulators that control pre-messenger RNA-splicing. Inactivation of MBNL can lead to myotonic dystrophy in adults. MBNL is mainly expressed in skeletal muscle, neuron tissue, thymus, liver, and kidney and plays an important role in the ultimate differentiation of muscle cells and neurons. MBNL1 is a member of the MBNL protein family. The inactivation of MBNL1 protein is particularly important in the development of myotonic dystrophy and can lead to cataract formation, abnormal muscle relaxation, cardiac and neurological dysfunction, etc. The induction of MBNL1 in tumors is known to significantly inhibit tumor progression and thus significantly prolong survival. MBNL1 antisense protein MBNL1-AS1 also plays an important role in tumor migration and development. Objective: This review reveals the role of MBNL1 and MBNL1-AS1 in the complex pathogenesis of many tumors, which provide a new target for the treatment of tumors. Methods: Correlated research are systematically retrieved via PubMed. In this review, the role of MBNL1 and MBNL1- AS1 were analyzed. Results: MBNL1 is down-regulated in breast cancer, leukemia, stomach cancer, esophageal cancer, glioma, and Huntington's disease. The function of inhibiting tumor cell metastasis decreased. It is up-regulated in cervical cancer and colorectal cancer, which can promote the development of tumor cells. Antisense protein MBNL1- AS1 can inhibit tumor cell proliferation and metastasis in colorectal cancer, non-small cell lung cancer, and gastric cancer. Conclusion: MBNL1 is an important regulator of tumor metastasis and growth, which exhibits a promising therapeutic target and can be further explored.
Keywords: migration